Большая книга о военной технике. 1001 фотография - Ликсо Вячеслав Владимирович (АСТ, 2023)
Экземпляры: ф.9 (20240507) / Инвентарный номер: 67863 / Цена: 1299.00 / Авт.знак: Л 56 / ГРНТИ: 03 / ББК: 68.8я 2